Methodological Problems of Psychometric Tests in Clinical Studies of Cognitive Disorders in Patients with Cerebral Vascular Lesions: a Review - Alina D. Aizenshtein; Aleksandra K. Trofimova; Yuri V. Mikadze; Galina E. Ivanova (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
AIM. To assess cognitive dysfunction in clinical practice, depending on the task being solved in the examination, different neuropsychological research methods are used. To identify the specific cause of the dysfunctions in the structure of various mental functions (neuropsychological characteristics of the defect) and in the brain functions (topical diagnosis), methods of qualitative analysis of the detected symptoms of the disorder are used. Psychometric (quantitative) methods are used to assess numerically the severity of disorders and the dynamics of changes in the state of individual mental functions, as well as for screening assessment of e possible cognitive decline level in general. Methods of cognitive dysfunctions qualitative assessment are focused on the search for a «missing link» in the structure of the examined mental functions. Psychometric tests, in most cases, describe the general state of either individual mental functions, or, in the case of screening, a set of cognitive functions. Thus, one or more aspects of mental functions are evaluated, in which several cognitive functions are involved at once. The article presents the results of a literature review with a description and analysis of preferences, methods used and corresponding techniques for neuropsychological examination of cognitive disorders in domestic clinical practice in vascular brain lesions.